A High-Precision and Wideband Fundamental Frequency Measurement Method for Synchronous Sampling Used in the Power Analyzer - Wang, Yifan; Chen, Kai; Gou, Xuan; He, Renjun; Zhou, Wenjian; Yang, Sheng; Qiu, Gen (Frontiers in Energy Research, 2021)
In the dedicated high-precision power quality analyzer, the synchronous sampling is required to reduce the effect of spectrum leakage produced by the Discrete Fourier Transform process. Thus, accurate fundamental frequency measurement is urgently needed. However, due to the harmonics and noise in the power signal, the accurate fundamental frequency measurement is difficult to achieve. Moreover, with the wide application of high-frequency programmable power supply, the fundamental frequency is gradually increasing, which requires power analyzers have the abilities of both high precision and a wide range of the fundamental frequency measurement. To solve these issues, a new fundamental frequency measurement architecture used in synchronous sampling is proposed. This architecture consists of a small-point Fast Fourier Transform module, spectrum refinement algorithm, and a multimodal optimization method to calculate the accurate fundamental frequency under large harmonic conditions. In the practical hardware platform results, this architecture has a large fundamental frequency measurement range from 20Hz to 200 kHz with a relative error which is less than 0.004%. The wideband fundamental frequency measurement structure proposed in this paper achieves high measurement accuracy.